How Safe Are Biological Agents in Pediatric Rheumatology? - Emine Nur Sunar Yayla; Çisem Yıldız; Pelin Esmeray Şenol; Nihal Karaçayır; Deniz Gezgin Yıldırım; Sevcan A. Bakkaloğlu (Turkish Archives of Pediatrics)
Objective: Biologic therapy has changed the prognosis of patients with rheumatologic disease. Despite all benefits of the biological agents, adverse events may occur due to their long-term use. The aim of this study is to analyze the adverse events observed in pediatric patients who received biological treatment.